Regional differences in cortical porosity in the fractured femoral neck. - Bell, K; Loveridge, N; Power, J; Garrahan, N; Meggitt, B; Reeve, J (1999)
Although bone mass is a contributory risk factor for intracapsular hip fracture, its distribution and porosity within the femoral neck is also important for bone strength. In femoral neck biopsies from 13 women with intracapsular hip fracture (mean +/- SEM: 75.4+/-2.1 years, OP) and 19 cadaveric samples (9 men and 10 women [control], aged 79.4+/-1.7 years), a segmental analysis was used to quantify circumferential variations in the characteristics of cortical bone haversian systems. In female control femoral necks, there was an increasing porosity gradient between the inferior (I) (7.7+/-0.6%) and superior regions (S) (16.05+/-1.8%,p < 0.005). In walking, these regions undergo compression and tension, respectively. In men, a similar trend was observed, but the differences were not significant (I: 11.1+/-1.2%; S: 14.1+/-1.7%; p = 0.133). This porosity gradient was not maintained in the fracture group (I: 10+/-1%; S: 12.65+/-1.2%). In contrast, porosity in the fracture group was greatest in the anterior cortex, being 41% higher in that quadrant than in controls (p = 0.06). The areal density of haversian canals ranged from 16.7 to 21.3 canals/mm2 with no significant differences between fractures and controls. In the control women, mean canal diameter was highest in the superior region (60+/-2.8 microm), and these canals were significantly larger than those in the inferior region (49.4+/-1.4 microm, p < 0.05). This difference was less marked in the fracture cases (I: 53.21+/-2.5 microm; S: 59.1+/-2.8 microm; p = 0.0878). Although the mean canal diameter in the anterior quadrant of the fracture cases was higher than in the control women this did not reach significance (OP/F: 59.5+/-3 microm; control/F: 52.7+/-2.6 microm; p = 0.106). However, the proportion of "giant" canals with diameters >385 microm (defined as the top 0.5% in the controls) was doubled in the anterior region of the fracture cases (OP/F: 1.28%; control/F: 0.69%; p < 0.005). Porosity is related to the square of the canal radius; therefore, such canals make a substantial contribution to cortical porosity. Previous work has shown that the elastic modulus of bone decreases approximately as the square root of porosity. Therefore, the increased porosity and the higher prevalence of "giant" canals have a markedly negative influence on the ability of the cortical shell to withstand stresses associated with a fall. The mechanisms responsible for the localized generation of "giant" haversian canals, and ultimately the "trabecularization" of the cortex, require further investigation.